Resistência à corrosão e à oxidação dos aços AISI 316L e SAF 2304 revestidos por ZrN e ZrSiN pela técnica de magnetron sputtering reativo - Fernanda de Lima Menezes (2019)
The use of the coatings to improve the material properties is an alternative for the development and application of new materials. ZrN and ZrSiN films are known for their good mechanical properties, but there are just few researches that investigate their corrosion resistance, making them applicable to fluid storage and transport systems. In this sense, this work proposes the study of ZrN and ZrSiN films deposited on 316L stainless steel and 2304 duplex steel. These steels are used in the construction of flexible tubes for multiphase fluids transportation, as petroleum industries. In this reserch, was studied the influence of substrate on the corrosion resistance of coating/substrate systems and the influence of silicon concentration on ZrSiN film. NaCl 3.0 % w/v was used as electrolytic solution at room temperature. The silicon content in ZrSiN film were between 0 and 12.3 at %. Electrochemical impedance spectroscopy (EIS) and anodic potentiodynamic polarization tests were used to analyze the corrosion resistance. The corrosion protection properties were collected after a short immersion time, at most 2 hours, and after a long immersion time, 1000 h total. According to electrochemical techniques results, for both substrates, the ZrN and ZrSiN films improved the corrosion resistance. The addition of Si increased the charge transfer resistance for 2304 duplex steel substrate, but the same was not observed for 316L stainless steel. It was also concluded that the substrate has influence on the film’s corrosion resistance. In this work, film/duplex steel 2304 systems presented better corrosion properties compared to film/316L stainless steel systems. Samples analyzed during 1000 hours of immersion showed that corrosion resistance tends to increase with immersion time. The films porosity was also calculated using the electrochemical data. Oxidation resistance at high temperatures, of 700, 800 and 1000oC, was studied as well. Using the X-ray diffraction technique, it was observed that the ZrSiN film has higher oxidation resistance than the ZrN film. X-ray photoelectron spectroscopy was used to determine the films chemical composition and thickness. ZrN and ZrSiN films thickness have approximately 200nm. By the scanning electron microscopy, it was found that the morphology of oxidized films tends to be less homogeneous with increasing temperature.